2009
DOI: 10.1038/sj.bjc.6605360
|View full text |Cite
|
Sign up to set email alerts
|

Change in the hormone receptor status following administration of neoadjuvant chemotherapy and its impact on the long-term outcome in patients with primary breast cancer

Abstract: BACKGROUND: To evaluate the impact of change in the hormone receptor (HR) status (HR status conversion) on the long-term outcomes of breast cancer patients treated with neoadjuvant chemotherapy (NAC). METHODS: We investigated 368 patients for the HR status of their lesions before and after NAC. On the basis of the HR status and the use/non-use of endocrine therapy (ET), the patients were categorised into four groups: Group A, 184 ET-administered patients with HR-positive both before and after NAC; Group B, 47 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 12 publications
6
61
2
Order By: Relevance
“…Cytotoxic, endocrine and biological agents may specifically target and kill sensitive BC subpopulations, leaving behind the resistant ones. This hypothesis was sustained by some studies, showing higher frequency of BC phenotype change in NAC-treated patients than in naïve controls [14,15]. The present work shows that most cases undergoing phenotype changes presented with advanced stage (pT3-4, pN+, cM+).…”
Section: Discussionsupporting
confidence: 83%
“…Cytotoxic, endocrine and biological agents may specifically target and kill sensitive BC subpopulations, leaving behind the resistant ones. This hypothesis was sustained by some studies, showing higher frequency of BC phenotype change in NAC-treated patients than in naïve controls [14,15]. The present work shows that most cases undergoing phenotype changes presented with advanced stage (pT3-4, pN+, cM+).…”
Section: Discussionsupporting
confidence: 83%
“…8 Few studies have investigated the association between biomarker status alterations and long-term outcomes, finding inconsistent results. [9][10][11] Furthermore, little is known about the relationship between alterations in receptor status after NCT and long-term survival outcomes. 12 The objectives of this study were to assess the frequency of ER, PR, and HER2 status changes and changes in breast cancer subtypes after NCT and to determine whether these changes were correlated with long-term survival outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…after neoadjuvant chemotherapy was reported in several studies (112)(113)(114). In general, studies that reported a good concordance of hormone receptor status before and after neoadjuvant chemotherapy had a relatively smaller number of patients compared to the studies that found significant changes.…”
Section: Serial Changes In Expression Of Proteins In Response To Neoamentioning
confidence: 76%